Progress in High-Pressure Co2–Ionic Liquid–Organic Compound Phase Equilibria and Their Applications: A Review - Romero-Figueroa, J (Elsevier B.V., 2026)
Carbon dioxide (CO2) and ionic liquids (ILs) have emerged as versatile solvents to facilitate green chemistry and engineering processes, and enable novel approaches to chemical reactions, separations, and purification processes. The tunable solvent properties of CO2 (density, solvent strength, selectivity), low toxicity, and low critical conditions make it an efficient medium for reaction and extraction, while ILs negligible volatility and customizable physicochemical properties offer unique opportunities for implementation in more sustainable applications. Despite extensive studies on CO2 + IL binary systems, careful study of the phase behavior upon integration of organic compounds into ternary CO2 + IL systems remains relatively underexplored. Nonetheless, there have been many clever ideas proposed and investigated for taking advantage of CO2+ IL + organic (or aqueous) solvent systems. This review focuses on the vapor-liquid (VLE) and vapor-liquid-liquid (VLLE) equilibrium behaviors of these ternary systems, emphasizing their application in catalytic and separation processes. Key findings reveal the potential of CO2 to act as an antisolvent, inducing phase splitting to separate organic compounds from ILs, while enhancing reaction kinetics by reducing IL viscosity and improving mass transfer. Hydrogenation, hydroformylation, oxidation, electro-oxidation, and biocatalysis applications demonstrate the effectiveness of CO2/IL systems in achieving high selectivity, enhanced conversions, and efficient catalyst recycling. Molecular simulations can further aid in the understanding of phase transitions and component interactions. Overall, this review underscores the potential of CO2 + IL systems to improve efficiency in production processes through innovative reaction and separation technologies. © 2025 Elsevier B.V.